Etika Pemimpin Dan Etika Memilih Pemimpin (Studi Pemahaman Masyarakat Desa Pantai Labu Pekan Tentang Hadis Mengenai Etika Pemimpin Dan Etika Memilih Pemimpin) - Maulida, Irma; Siregar, Muhammad Nuh (UIN Sumatera Utara Medan, 2024)
The background to the problem in this research originates from initial research, the researcher found that in Pantai Labu Pekan Village there were problems in the ethics of leaders and how to choose leaders, because what happened was not in accordance with Islamic law. The ethics of selecting leaders in Pantai Labu Pekan Village there were still many people who still accepting bribes while before voting Meanwhile the author has found a Hadith narrated by al-Hakim which talks about voting and accepting bribes.This research uses qualitative methods with descriptive data analysis, which refers to the contribution of data to efforts to answer the problem formulation and research focus. Data collection techniques include participant observation, structured art interviews, and documentation. The results of the research revealed that there are still many in Pantai Labu Pekan Village who do not understand the Hadith to be associated with the second source of law after al-Quran. And with the research in this village. Hadith that the author carefully has relevance, namely the provision of the community before carrying out their mandate, and before choosing a leader in accordance with Islamic law.